2019
DOI: 10.5152/tud.2018.97345
|View full text |Cite
|
Sign up to set email alerts
|

Observational prospective study for surgical outcome and anesthetic feasibility of tubeless and totally tubeless supine PCNL: A single centre initial experience

Abstract: Objective: To evaluate surgical outcome and spinal anesthetic feasibility of supine percutaneous nephrolithotomy (PCNL) by tubeless and totally tubeless method. Material and methods: This observational study included a totally 53 patients. Initial diagnosis of renal stone was based on urinary ultrasonography, kidney, ureter and bladder X-ray, and later confirmed by computed tomography urography. PCNL was done with the patient in Galdakao-modified supine Valdivia position. Nephrostomy was not done using tubeles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Recently, new modifications were described by the miniaturization of instruments as external ureteral catheterization and totally tubeless PCNL. [12][13][14] These modified techniques were safe and effective and further improve patient comfort after the operation. We use this procedure in daily practice but, we did not include this group in our study due to the limited number of cases.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, new modifications were described by the miniaturization of instruments as external ureteral catheterization and totally tubeless PCNL. [12][13][14] These modified techniques were safe and effective and further improve patient comfort after the operation. We use this procedure in daily practice but, we did not include this group in our study due to the limited number of cases.…”
Section: Discussionmentioning
confidence: 94%
“…We performed four (20%) tubeless PCNLs, which have the benefit of less postoperative discomfort. Supine and tubeless PCNL offer beneficial effects for both surgeries [ 7 ]. It has been shown that, in carefully selected patients, tubeless PCNL is a safe option [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 The low rate of complications in our cohort support the safety of POD1 stent removal and consideration of more study and/or more widespread adoption, particularly considering the similar success rates of totally tubeless approaches. 4,19 A short-term indwelling stent over a "totally tubeless" approach has some potential advantages. Stenting with a Foley allows renal decompression after this procedure and provides for the rapid identification of patients with severe bleeding that may need additional procedures.…”
Section: Discussionmentioning
confidence: 99%